2008
DOI: 10.1111/j.1365-2834.2008.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the evidence-based practice maze

Abstract: Multiple ways of knowing, or evidence, for informed clinical decision making must be considered based on situational context. No hierarchy fits all situations. Nurses must provide support and resources to facilitate nurse empowerment; nurses are accountable for using EBP to enhance patient outcomes. Implications for nursing management Effective EBP implementation relies on nurses being cognizant of what current nursing EBP trends are based on and where they are going. Nurses have a key role in facilitating con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Utility of MEWS/EWS systems. Although systematic reviews and meta‐analyses of randomized controlled trials (RCTs) are regarded as the ‘gold standard’ of evidence on which to base practice (Hudson et al. 2008, Grimes & Schulz 2002), the evidence‐based practice (EBP) movement has been criticized for its authoritarian approach (Holmes et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utility of MEWS/EWS systems. Although systematic reviews and meta‐analyses of randomized controlled trials (RCTs) are regarded as the ‘gold standard’ of evidence on which to base practice (Hudson et al. 2008, Grimes & Schulz 2002), the evidence‐based practice (EBP) movement has been criticized for its authoritarian approach (Holmes et al.…”
Section: Resultsmentioning
confidence: 99%
“…Although RCTs are considered the strongest form of evidence, the complexity of introducing an EWS system, with an accompanying educational programme and audit, might suggest that a single RCT of an early warning scoring system might be almost impossible (Quarterman et al. 2005, Grypdonck 2006, Hudson et al. 2008): it would be impracticable to randomize individual patients on the same ward to receive different levels of monitoring (Robson 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Nursing BPGs are one source of knowledge available to nurses to support the integration of evidence into practice [48][49][50] . In this guideline, we outline recommendations for nursing practice, education, the organization of health services and policy development specifically in relation to dyspnea and COPD.…”
Section: Guideline Recommendationsmentioning
confidence: 99%
“…However, the implementation of basic research discoveries into daily clinical practice remains inconsistent and presents complex challenges (Aarons, 2005;Melnyk & Fineout-Overholt, 2005;Melnyk, Fineout-Overholt, Giggleman, & Cruz, 2008;Titler, 2007;Wilkenson et al, 2011). The nurse in practice stands at the forefront of this movement and is asked to embrace a new era for nursing and patient care, which will require changes in the education of students, more relevant clinical research, and EBP education (Gale & Schaffer, 2009;Hudson, Duke, Haas, & Barnell, 2008;IOM, 2011;Rycroft-Malone, 2008a, 2008bScott & McSherry, 2008). Gifford and colleagues (2007) found that leadership activities can enhance, influence, and stimulate the intrinsic moti- vation of the nurse to use research in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%